2014
DOI: 10.1080/15248372.2013.803971
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Measurement of the Components of Attention With Young Children Using the Attention Network Test: Stability, Isolability, Robustness, and Reliability

Abstract: The current study examined the robustness, stability, reliability, and isolability of the attention network scores (alerting, orienting, and executive control) when young children experienced repeated administrations of the child version of the Attention Network Test (ANT; Rueda et al., 2004). Ten test sessions of the ANT were administered to 12 young children. Participants were asked to indicate the direction of a target fish, flanked by distractors, presented either above or below the fixation cross followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Rueda et al (2004) developed a child-friendly version of the ANT in which the stimuli were line drawings of fish that faced left or right, with the target fish flanked by congruent or incongruent distractor fish. Congruency effects were obtained, but they were not reliably modulated by the cues that preceded the stimuli, despite evidence that the cues increased alertness (see also Ishigami & Klein, 2015). Alerting-congruency interactions also appeared to be absent for children and adults who performed versions of the ANT with fish, schematic faces, or real faces as stimuli (Federico,Marotta,Adriani,9 Some readers might wonder about the probability of obtaining significant effects in all nine experiments, in light of analyses of the literature (e.g., Francis, 2014;Francis, Tanzman, & Matthews, 2014) that have revealed a prevalence of excess success in psychology studies (i.e., more significant effects in a set of experiments than would be expected, based on estimates of effect size and power).…”
Section: Statistical and Methodological Considerationsmentioning
confidence: 96%
“…Rueda et al (2004) developed a child-friendly version of the ANT in which the stimuli were line drawings of fish that faced left or right, with the target fish flanked by congruent or incongruent distractor fish. Congruency effects were obtained, but they were not reliably modulated by the cues that preceded the stimuli, despite evidence that the cues increased alertness (see also Ishigami & Klein, 2015). Alerting-congruency interactions also appeared to be absent for children and adults who performed versions of the ANT with fish, schematic faces, or real faces as stimuli (Federico,Marotta,Adriani,9 Some readers might wonder about the probability of obtaining significant effects in all nine experiments, in light of analyses of the literature (e.g., Francis, 2014;Francis, Tanzman, & Matthews, 2014) that have revealed a prevalence of excess success in psychology studies (i.e., more significant effects in a set of experiments than would be expected, based on estimates of effect size and power).…”
Section: Statistical and Methodological Considerationsmentioning
confidence: 96%
“…The orienting network is believed to be stable during infancy and adulthood (from age 6; Gupta & Kar, 2009;Ishigami & Klein, 2015;Rueda et al, 2004), but it has a peak during adolescence (Mezzacappa, 2004). However, research on preschoolers has suggested that the results of the cueing conditions may not be as straightforward as initially claimed (Rueda et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although the ANT is generally recommended for use with children as young as 4 years of age, only a few studies have focused on this particular age group and, to our knowledge, no study has used the ANT to evaluate children under the age of 4. Moreover, some studies that have included a preschool sample have found inconsistent results (Forns et al, 2014;Ishigami & Klein, 2015;Rueda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The condition specifically dedicated at the estimation of the alerting and orienting networks performance could improve the measure of each attentional networks (Ishigami, & Klein, 2010). In addition, the ANT was often perceived as long and boring by the children (Ishigami & Klein, 2015). Although we had few omission errors, this boring aspect of this task can have an impact on children's motivation and on the accuracy of attentional measures.…”
Section: Limitations Of Our Studymentioning
confidence: 92%